Streamlining B2B Communication in the SAP Ecosystem : Custom Mapping Solutions for Enhanced EDI Processing (International Journal of Scientific Research in Science and Technology, 2024)
In our paper, we delve into the realm of enhancing business-to-business (B2B) communication within the SAP ecosystem by focusing on the development of custom mapping solutions. Our primary objective is to streamline Electronic Data Interchange (EDI) processing through the creation of tailored mappings within the SAP Integration Suite. Specifically, we explore the design of mappings for SAP Integration Suite’s Trading Partner Management (TPM) agreements and Message Implementation Guidelines (MIG) objects. Our approach involves employing graphical, XSLT, and graphical mappings to ensure compatibility with EDI requirements. We also emphasize the importance of thorough testing to validate the effectiveness of our mapping solutions. Through our research, we aim to contribute to the optimization of B2B communication processes, ultimately fostering greater efficiency and reliability within the SAP ecosystem.